THE USE OF ORIGAMI PAPERS TO PRACTICE ENGLISH SPEAKING - Nikmah Khairani; Sarah Anggraini (Journal of Advances in Linguistics and English Teaching (JALET), 2025)
This research aims to explore origami as a method to assist students inlearning more effectively. Microteaching is a method that helps teachersimprove their skills, and this study tests whether origami can be a useful tool.Researchers asked 12th-grade students at a school named SMA Negeri 2Panyabungan to try origami in their lessons. They observed the students,at aschool named SMA Negeri 2 Panyabungan to try origami in their lessons.They observed the students, discussed it afterward, and gathered theiropinions. The results indicate that using origami helps students becomebetter teachers, enhances communication skills, and fosters creativity.Origami makes learning more enjoyable and interactive. This researchcontributes to understanding the significant benefits of origami in teachingand provides insights on how to enhance teaching practices.